Histórias e memórias do ensino de educação física nas escolas normais Duque de Caxias e São José de Caxias do Sul/RS (1947-1961) - Giacomoni, Cristian (My University, 2022)
This thesis, developed at the Graduate Program in Education at the University of Caxias do Sul, has a historical character and its main objective is to analyze how Physical Education developed at the Escola Normal Duque de Caxias (ENDC) and at the Escola Normal São José (ENSJ), between 1947 and 1961, made it possible to identify and understand how the formative processes of these classes and practices were evidenced in the documents and memories of teachers and teaching students, imbricated in these institutions. The temporal space approach adopted researched the two Normal Schools in their first spaces and times, when they were still located in the central area of Caxias do Sul. It begins in 1947, the year of foundation of the ENSJ, and ends in 1961, the year of the change of address of ENDC, which now shares a new space with another educational institution. The theoretical assumptions are supported in Cultural History by the possibilities of showing and analyzing social and educational manifestations of certain groups and institutions, as well as a very wide range of aspects related to culture. The methodology adopted is Oral History and Historical Document Analysis, through semi-structured interviews with three Physical Education teachers, Aura Ribeiro Mendes da Silva, Gemma Catharina Maria Martinato Callegari and Julita Luiza Schumacher Stallivieri, three teaching students, Edelweiss Rossarolla Soares, Carmen Lucia Duso Ribeiro Mendes and Suzana Eleonora Corsetti Mancuso, and through the mobilization of historical and institutional documents, laws, decrees, minutes, reports, books, notebooks, newspapers and photographs researched in different collections in the state of RS. The thesis is organized into three main axes of discussion. The first contextualizes the city of Caxias do Sul between 1947 and 1961, presents the social, educational, and political movements for the creation of ENDC and ENSJ, and discusses how the implementation and main training processes of Physical Education in these schools took place. The second axis analyzes the first movements in the search of specialized teacher training for school Physical Education in RS, aiming to understand how the formative resonances of the Intensive Physical Education Course and the Higher School of Physical Education (ESEF) intertwined with pedagogical currents prioritized by teachers responsible for the discipline at ENDC and ENSJ. And, finally, the third axis aimed to understand how a mode of teacher training in Physical Education was developed in the teaching education in Caxias do Sul, in addition to analyzing the practices, spaces, and materiality?s as elements of school culture used by the teachers. It also analyzes how these classes contributed to the constitution of professional identities and fostered the development of habits and customs of bodily practices. The researched evidence made it possible to identify that the formative processes were divided between two areas. The first of a biological, physiological, and physical nature, with classes organized by different gymnastic and sports exercises, the requirement of technical execution of movements, the development of harmony and precision in body gestures, and the use of these as a hygienic instrument aimed at preventing diseases, correct and improve the physical deficiencies of the teaching students. The second guided the teaching of strategies, didactics, and pedagogies on how to teach Physical Education to primary education, observing children's characteristics and the spatial and material elements of school groups in the region, through games, relay race, classroom practices, and activities related to local culture. Thus, the thesis is that Caxias do Sul was constituted as a training center for Physical Education teachers, as a result of the formative resonances that begin in the Intensive Course, permeate through the ESEF, and are perpetuated in the different social relationships established between the teachers and the teaching students, in the sharing, debates, and reflections of knowledge and theoretical and practical experiences, in view of the changes that are perceived both in the organization, planning, as well as in practices and in the constitution of a local school culture. These processes brought better pedagogical and didactic preparation, expanded and diversified the practices learned and appropriated by future teachers who taught Physical Education, had repercussions at school, social and cultural levels, and enabled the projection of other teachers in national and international spheres. [resumo fornecido pelo autor]
Esta tese, desenvolvida junto ao Programa de Pós-Graduação em Educação da Universidade de Caxias do Sul, possui caráter histórico e tem como objetivo principal analisar como a Educação Física desenvolvida na Escola Normal Duque de Caxias (ENDC) e na Escola Normal São José (ENSJ), entre 1947 a 1961, possibilitou identificar e compreender como os processos formativos destas aulas e práticas se evidenciaram nos documentos e nas memórias de professoras e de normalistas imbricadas nestas instituições. O recorte espaço-temporal adotado pesquisou as duas Escolas Normais nos seus primeiros espaços e tempos, quando ainda estavam localizadas na área central de Caxias do Sul. Tem início em 1947, ano de fundação da ENSJ, e finda em 1961, ano da mudança de endereço da ENDC, que passa a dividir um novo espaço com outra instituição escolar. Os pressupostos teóricos estão sustentados na História Cultural pelas possibilidades de evidenciar e analisar manifestações sociais e educacionais de determinados grupos e instituições, bem como uma gama muito grande de aspectos ligados à cultura. A metodologia adotada é da História Oral e da Análise Documental histórica, mediante entrevistas semiestruturadas com três professoras de Educação Física, Aura Ribeiro Mendes da Silva, Gemma Catharina Maria Martinato Callegari e Julita Luiza Schumacher Stallivieri, três normalistas, Edelweiss Rossarolla Soares, Carmen Lucia Duso Ribeiro Mendes e Suzana Eleonora Corsetti Mancuso, e pela mobilização de documentos históricos, institucionais, leis, decretos, atas, relatórios, livros, cadernos, jornais e fotografias pesquisados em diferentes acervos do RS. A tese está organizada em três grandes eixos de discussão. O primeiro contextualiza o município de Caxias do Sul entre 1947 e 1961, apresenta os movimentos sociais, educacionais e políticos para a criação da ENDC e da ENSJ e discute como ocorreu a implementação e os principais processos formativos de Educação Física nessas escolas. O segundo eixo analisa os primeiros movimentos em busca de uma formação especializada para Educação Física escolar no RS, visando compreender como as ressonâncias formativas do Curso Intensivo de Educação Física e da ESEF se imbricaram às correntes pedagógicas priorizadas pelos professores responsáveis pela disciplina na ENDC e na ENSJ. E, por fim, o terceiro eixo visou compreender como foi desenvolvida na formação normalista caxiense um modo de constituição docente em Educação Física, além de analisar as práticas, os espaços e as materialidades como elementos da cultura escolar utilizados pelas professoras. Ainda analisa como essas aulas contribuíram para a constituição de identidades profissionais e propiciaram o desenvolvimento de hábitos e costumes de práticas corporais. Os indícios pesquisados possibilitaram identificar que os processos formativos eram divididos entre dois âmbitos. O primeiro de caráter biológico, fisiológico e físico, com aulas organizadas pelos diferentes exercícios ginásticos e esportivos, pela exigência da execução técnica dos movimentos, pelo desenvolvimento da harmonia e precisão nos gestos corporais, e pela utilização destes como instrumento higiênico que visava a prevenir doenças, corrigir e aprimorar deficiências físicas das normalistas. O segundo orientou para o ensino de estratégias, didáticas e pedagogias de como ensinar Educação Física ao ensino primário, observando as características infantis e os elementos espaciais e materiais dos grupos escolares da região, mediante brincadeiras, estafetas, práticas em sala de aula e atividades relacionadas à cultura local. Desse modo, a tese é de que Caxias do Sul constituiu-se como um polo potencial formador de professores de Educação Física, resultado das ressonâncias formativas que iniciam no Curso Intensivo, perpassam pela ESEF e se perpetuam nas diferentes relações sociais estabelecidas entre as professoras e as normalistas, nas partilhas, debates e reflexões de conhecimentos e de experiências teóricas e práticas, tendo em vista as mudanças que são percebidas tanto na organização, planejamento, quanto nas práticas e na constituição de uma cultura escolar local. Esses processos trouxeram um melhor preparo pedagógico e didático, ampliaram e diversificaram as práticas aprendidas e apropriadas pelas futuras docentes que lecionaram Educação Física, repercutiram a nível escolar, social e cultural, e propiciaram a projeção de outros professores a âmbitos nacionais e internacionais. [resumo fornecido pelo autor]
Keywords: Educação física - Estudo e Ensino - História; Escolas - Caxias do Sul (RS) - História; Memória coletiva; História oral; Physical education and training - Study and teaching - History; School - Caxias do Sul (Brazil) - History; Collective memory; Oral history